(untitled) (Hematology Meeting Reports, 2009)
Since the technology for the isolation of Hodgkin/Reed-Sternberg cells (H/RS) was developed, there has been a great improvement in the understanding of the pathogenesis of the disease. Hodgkin cell lines have been used extensively in basic research, but there may be intrinsic biologic differences between the in situ H/RS cells in primary tumors and the few cell lines derived from such tissues. Nevertheless, new and unique biologic information has also been derived from cell lines which has only partially correlated with in situ disease in the design of new therapies.1 This paper will outline some of the newer biologic investigations that have generated potential therapeutic agents and some in early clinical trials. None have reached the point of approval by regulatory agencies but do offer the hope that targeted agents could emerge that do not possess overlapping toxicity to currently effective myelotoxic agents and may be combined with active regimens or given in sequence to them.